THE DEVELOPMENT OF DIGITAL BANKS IN 2021 - Nadira Nur Affiah Heryanto (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
Digitalization that occurs also has an effect on banking services. Banks must be able to be in line with technological developments and the digital world. With this, banks bring up new innovations to be able to compete with Digital Banks and also digital payment systems that have already helped the wider community. This research shows that the Bank continues to move along with the development of the world, as now banks are moving along with the development of the digital era. And also in this study it is shown that banks that have an important role in economic growth continue to create innovations according to people's behavior so that banks are not left behind.